Induction motors versus permanent magnet actuators for aerospace applications - Kakosimos, Panagiotis E.; Sarigiannidis, Athanasios G.; Beniakar, Minos E.; Kladas, Antonios G.; Gerada, C. (Institute of Electrical and Electronics Engineers, 2014)
This paper introduces a comparative study on the design of aerospace actuators concerning Induction Motor (IM) and Permanent Magnet Motor (PMM) technologies. In the analysis undertaken, the two candidate configurations are evaluated in terms of both their electromagnetic and thermal behavior in a combined manner. On a first step, the basic dimensioning of the actuators and their fundamental operational characteristics are determined via a time-stepping Finite Element (FE) analysis. The consideration of the thermal robustness of the proposed motor configurations is integrated in the design procedure, through the appropriate handling of their respective constraints. As a result, all comparisons are carried out on a common thermal evacuation basis. On a second step, a single objective optimization procedure is employed, considering several performance and efficiency indexes using appropriate weights. Manufacturing and construction related costs for both investigated topologies are considered employing specific penalty functions. The impact of the utilized materials is also examined. The resultant motor designs have been validated through manufactured prototypes illustrating their suitability for aerospace actuation